Studi Deskriptif tentang Hubungan Kehadiran dan Prestasi UAS pada Mata Kuliah Dasar Kewirausahaan Mahasiswa Pendidikan IPA UNM Angkatan 2024 - Salma Samputri (JAMBURA Elementary Education Journal, 2025)
This study is a analyze the relationship between attendance scores and Final Semester Examination (UAS) achievements in the Basic Entrepreneurship course for students of the Science Education Study Program at Makassar State University class of 2024. The data used includes attendance scores and UAS scores from 29 students. The analysis results show that the average student attendance score is 81.4, while the average UAS score is 64.1. Pearson correlation analysis resulted in a coefficient value of 0.717 with a significance value of p < 0.001, which indicates a strong and significant positive relationship between attendance scores and final exam grades. This finding confirms that the level of student attendance greatly influences the achievement of final exam scores in entrepreneurship courses. Therefore, increasing the discipline of attendance and active involvement in the learning process is the key to student academic success